(untitled) (Tempo e Argumento, 2022)
This article departs from a comparative exercise concerning the sixth-grade school in Brazil (11-year-old students, on average) and the third cycle of primary in Québec (students from 11 to 12 years-old). Both a historian and a pedagogue undertake comparative analysis of the school curricula in these two educational realities. From this hermeneutic strategy, we put under discussion certain themes related to the sixth grade in Brazil, along with the respective contents of the third cycle primary in Québec. Regarding the tensions between Education and History, this article aims to examine the learning of History at schools, primarily speaking of the curricular construction, the development of competencies, and of historical thinking specifically.